Diseño de una metasuperficie usando la teoría de modos característicos para reducir el radar Cross Section - Gonzalez Cevallos, Juan Carlos (2022)
The present research project aims at the design and simulation of a metasurface through the theory of characteristic modes (TCM) that will be used to reduce the radar cross section (RCS). The antenna has been designed and evaluated in the electromagnetic simulator CST Studio Suite, which operates in a frequency range from 3.41 GHz to 6.77 GHz, it is established on a substrate with dielectric permittivity εr = 4.4 (FR-4), subsequently Altair FEKO is used to describe the behavior of the antenna using the Theory of Characteristic Modes, thus obtaining the parameters that describe the operation of the antenna both in transmission and reception. In addition, the structure is evaluated using monostatic RCS simulations to check the reduction of the Radar Cross Section. Once the information on the antenna parameters has been obtained, a comparison is made with the meta- surface results developed by various authors. The research project consists of 5 chapters. The first chapter addresses the statement of the problem and the objectives to be achieved by carrying out the research. Moving forward, in the second chapter, the current state of the topics related to the research is contemplated, as well as the theoretical support that bases the processes carried out. Later, in the third chapter, the procedures used for the design and simulation of the structure are explained. Then, in the fourth chapter of the investigation, the results and operation of the metasurface are presented. And finally, in the fifth chapter the conclusions and recommendations of the research project will be established